О‘QUVCHILARNING LOYIHALASH MADANIYATINI SHAKLLANTIRISHDA TA’LIMIY ROBOTOTEXNIKADAN FOYDALANISH - Abdug‘aniyev, B.B. (SCIENCE and SOCIETY, 2022)
This article provides information on the conditions for the use of educational robotics in the formation of the design culture of school students.
Keywords: project; project culture; design formation; informatics and information technology; educational robotics